Social Media Influencer Communication Efficiency On Instagram - Novrian, Novrian (Universitas Gajah Putih, 2024)
These days, with the speed at which technology is developing, a lot of businesspeople employ digital platforms as a tool for their marketing strategies. There are advantages and disadvantages to the unrestricted flow of knowledge across time and place. The public's use of social media has changed as a result of the quickly evolving internet technologies. A true example of technological advancement from the emergence of new media is social media. Social media is an internet platform that facilitates communication between users. one of the phases of product marketing that involves developing a consumer perception of the brand. The capacity of customers or potential customers to recall a brand is known as its brand image. Endorsements are one method for doing this. Marketing communications has led to the current social media endorsement phenomena. Businesses use influencers, who are typically celebrities or well-known personalities with societal notoriety, to pique customers' interests. Determining Influencer Communication on Instagram Social Media is the aim of this study. Quantitative research methodology is applied. There were 51 responders in the sample. The correlation coefficient (r) between influencer communication and brand image is 0.325, indicating a somewhat good link, according to the findings of calculations performed with SPSS 25.